Cognitive ability and motor performances in the elderly - Jovanović, Stevan S.; Stojanović-Jovanović, Biljana N.; Pavlović, Aleksandra M.; Milošević, Radovan Lj.; Pavlović, Dragan M. (Vojnosanitetski pregled, 2022)
Background/Aim. Aging entails a wide range of cognitive processes that are not independent of one another. It leads to changes in physical-motor characteristics and sometimes to disability. The aim of this study was to examine the association between multiple cognitive performances in elderly subjects and their physical-motor abilities. Method. The study included 98 elderly participants (60+) (16 males and 82 females). Cognitive abilities were assessed by the Montreal Cognitive Assessment (MoCA)/Serbian version, and physical measures were assessed by the Senior Fitness Test with its five subtests, supplemented by the Walking Speed Test. Results. Several MoCA items demonstrated relatively low variability, i.e., they proved to be too easy for most of the participants. The participants exhibited the lowest performance on the memory relating to other domains, followed by executive functions, visuospatial skills, attention, concentration, and working memory domains, with the highest performance on temporal and spatial orientation relating to other domains. Executive functions and language correlated most significantly with physical strength. Agility and dynamic balance, lower- and upper-body strength, and aerobic endurance correlated moderately and positively. Conclusion. This study underlines the positive correlation between physical fitness and cognitive level in the elderly and emphasizes the importance of physical fitness for cognitive functions, especially those of executive type in elderly subjects. Clinicians should consider the association between cognitive function and physical-motor performances when dealing with functioning improvement in the elderly. The importance of designing the most efficient exercise programs to achieve maximal somatic and cognitive effects is emphasized.
Keywords: aging; cognition; exercises; aged; physical fitness